Exploring the underlying factors inducing design changes during building production - Yap, Jeffrey Boon Hui; Abdul-Rahman, Hamzah; Wang, Chen; Skitmore, Martin (Taylor & Francis, 2018)
Although design changes is a significant inhibiting factor to schedule management and cost control in building projects globally, however, the reasons remain largely unknown, and the construction industry is unable to manage the problem effectively. A triangulated approach was employed where 39 reasons were first explored through semi-structured interviews with experienced practitioners. Subsequently, a national survey was used to rank the reasons. ‘Value engineering’, ‘lack of coordination among various professional consultants’ and ‘change of requirement’ ranked the highest. Next, exploratory factor analysis revealed eight underlying factors. Finally, the influence of these manifested factors was validated statistically using partial least squares based structural equation modelling. The three most critical factors found are ‘competency of project team', ‘quality and workmanship’, and ‘site constraints and safety consideration’. This paper contributes to the development of new underlying factors inducing design changes, which largely explain design changes as well as enable practitioners and researchers to devise effective preventive measures in controlling design changes in building projects